Chiral Ag Nanostructure Arrays as Optical Antennas - Krstic, Vojislav; Gough, J. J.; McCloskey, D.; Caridad, J. M.; Krstic, V.; Muller, M.; Gaponik, N.; Bradley, A. L. (2015 9th International Congress on Advanced Electromagnetic Materials in Microwaves and Optics (METAMATERIALS), 2015)
Directional and circularly polarised emission from quantum dots coupled with chiral Ag nanostructures has been demonstrated. Semiconductor quantum dots were deposited onto the chiral structures using the Layer-by-Layer deposition technique. Time-resolved photoluminescence measurements demonstrated a lifetime quenching efficiency of 82%, confirming the strong interaction between the emitters and the antennas. Angle- and polarisation-resolved photoluminescence measurements revealed that the chiral nanostructures influence the far-field emission properties of the quantum emitters through dipole coupling. The far-field emission from the quantum dots coupled to the chiral nanostructures displays directionality in the emission pattern and more than 17% circular polarisation, following the handedness of the chiral structure.<br
UnivIS-Import:2017-12-18:Pub.2015.nat.dphy.IAP.LAP.chiral
Keywords: Antenna arrays; Indium tin oxide; Optical device fabrication; Optical polarization; Quantum dots; Solids; Substrates